Faktor yang berhubungan dengan Kelelahan Kerja Perawat di Rumah Sakit Umum Daerah Tarutung - Erna Dame Juliyanti Sihombing; Ermi Girsang; Santy Deasy Siregar (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2021)
The level of work-related fatigue experienced by workers can cause discomfort, annoyance and reduce satisfaction and decrease productivity. Nurse fatigue can have a negative impact in the process of handling patients seeking treatment at health services. The purpose of this study was to determine the factors associated with work fatigue on nurses at the Tarutung Regional General Hospital. This type of research is an analytic survey with a cross sectional design. The population of the study were 120 nurses at the Tarutung Regional General Hospital. The research sample was 92 nurses at the Tarutung Regional General Hospital, obtained using simple random sampling. Data collection techniques by means of observation and questionnaires. Based on the results of the Chi-Square test, it was found that there was a relationship between age and work fatigue with a p-value of 0.004, there was a relationship between work tenure and work fatigue with a p value = 0.001, there was a relationship between work shift and work fatigue p Value = 0,000, and the relationship between workload and work fatigue p Value = 0.000. The conclusion of the study is that there is a relationship between age, work period, work shift and workload associated with work fatigue on nurses at the Tarutung Regional General Hospital. It is advisable for workers to set a break time before doing night shift work which is more prone to work fatigue.